SIGNIFICANCE OF AHARA-VIDHI-VISHESHAYATAN IN TODAY’S ERA (International Journal of Ayurveda and Pharma Research, 2021)
Ayurveda is the science focusing on the way of living. It is a lifestyle which must be adopted for a healthy and sustainable living. Food has remained an important part of our cultures, faith, regions, communities etc. It is the basic requirement of life and plays a crucial role in the nourishment and protection of the beings. Food not only meets the bodily requirements but also nurtures the mind, senses and soul. In this regard we have the concept of Ashtahar vidhi visheshayatan, which emphasizes on the way and rules of dietetics. It emphasizes on the wholesomeness of the food and it’s considerations with respect to individuality. This age old concept is very much relevant in today’s time also. The following article focuses on this concept, its application and significance in modern era. Here we focus on these 8 factors individually and take detailed insight into this novel concept.